Development of a Smoking Device to Enhance Quality and Production of Smoked Fish - Nota Effiandi; Rahmat Hafis; Ichlas Nur; Muhammad Sabri; Ahmad Hasnul Fajri Arsyah (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
This study focuses on the design and development of a smoking device aimed at enhancing the quality and production efficiency of smoked fish. The primary objective was to create a device that optimizes the smoking process, ensuring consistent product quality while increasing production capacity. The development process involved a systematic design approach, including the selection of materials and construction techniques. The smoking process utilized a combination of drying and the application of natural smoke compounds derived from the combustion of organic materials. Performance testing was conducted using catfish as the primary substrate, with measurements taken for smoking duration, moisture content, and production rate. The effectiveness of the device was evaluated based on sensory characteristics, including texture, color, and aroma. The smoking apparatus was constructed with dimensions of 126 cm x 100 cm x 180 cm and is capable of accommodating up to 32 kg of fresh fish per smoking cycle. Results indicated that the smoking device achieves a production rate of 4 kg of smoked fish per hour, yielding products with a desirable golden-brown color and distinct smoky aroma. The findings demonstrate that the device significantly improves production capacity and allows for enhanced control over smoking conditions, contributing to greater consistency in product quality.